Peningkatan Literasi Budaya Anak-anak Panti Asuhan Amanda melalui Fabel Populer Dayak Maanyan: Enhancing the Cultural Literacy of Amanda Orphanage Children through Popular Dayak Maanyan Fables - Ramadhan, Ibnu Yustiya; Christy, Nirena Ade; Ferudyn, Ade Yusuf; Lestariningtyas, Stefani Ratu; Dewi, Sartika; Siallagan, Christian J (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This activity aims to introduce and preserve the Dayak Maanyan's local culture by reading popular fables to children at the Amanda Orphanage in Palangka Raya City, Central Kalimantan. The fable reading serves as a means to enhance cultural literacy among the children. This community service method involves interactive storytelling of Dayak Maanyan fables, designed to teach cultural values and foster children's imagination and critical thinking skills. Success indicators include the number of active participants, their understanding of local culture, increased creativity and expression, and feedback from the participants and orphanage administrators. Through this activity, orphanage children are expected to gain a deeper understanding of and appreciation for the Dayak Maanyan cultural heritage, contributing to its preservation.